Numerical simulation of metal removal in laser drilling using meshless local Petrov–Galerkin collocation method - Abidou, Diaa; Sarhan, Ahmed Aly Diaa Mohammed; Yusoff, Nukman; Nik-Ghazali, Nik Nazri; Awang, Md Abu Omar; Hassan, Mohsen A. (Elsevier, 2018)
A simplified 2D axisymmetric meshfree model of transient metal laser drilling is proposed for a continuous laser beam of Gaussian distribution. The penetration depth is predicted over the whole ablation time. The meshless local Petrov–Galerkin (MLPG) collocation method is used for discretizing the governing equation. Moving least square (MLS) and weighted least square (WLS) are used for approximating the local temperature field. The scheme is constructed in MATLAB, and the results are compared with previous numerical and experimental studies. The numerical results agree with the previous work, thus showing the models reliability in predicting the penetration depth for such a physically complex process.